2021
DOI: 10.1002/jso.26772
|View full text |Cite
|
Sign up to set email alerts
|

Allograft prosthetic composite reconstruction using a reverse total shoulder arthroplasty for failed oncologic proximal humerus reconstruction

Abstract: Introduction Endoprosthetic or allograft reconstruction are the preferred reconstruction techniques for proximal humeral bone tumors. Failure of these reconstructions may occur, but historically revision is performed rarely due to the lack of reliable options. Reverse shoulder arthroplasty with an allograft prosthetic composite (rAPC) may provide a revision option. The purpose of the current study was to evaluate our institutional outcome of these procedures. Methods Eleven (6 male, 5 female) patients (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Noncomparative studies had an average score of 12.3 6 0.9 while comparative studies averaged 18.5 6 0.6, indicating moderate quality of evidence. See Supplementary Table for individual studies and MINORS scores 2,6,7,[9][10][11][12][18][19][20][21][22][23][24][25][26] .…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Noncomparative studies had an average score of 12.3 6 0.9 while comparative studies averaged 18.5 6 0.6, indicating moderate quality of evidence. See Supplementary Table for individual studies and MINORS scores 2,6,7,[9][10][11][12][18][19][20][21][22][23][24][25][26] .…”
Section: Search Resultsmentioning
confidence: 99%
“…Similarly, APC fracture/fragmentation rates were reported by less than half of the included studies (6 of 16) 2,7,11,21,23,26 . The mean time to APC union was reported even less frequently (4 of 16) 2,6,21,23 . The heterogeneity in the radiographic assessment of APC reconstruction makes cross-study comparison difficult.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Re-revisions were required for 2 patients with allograft-related complications. The overall function improved significantly 33 . Finally, Jawad et al queried the SEER database for patients diagnosed with primary sarcomas originating from the bones of the hand and the wrist and reported that disease-specific survival was 90% at 5 years and 84% at 10 years 35 .…”
Section: Primary Bone Tumorsmentioning
confidence: 90%
“…Secondary to a historic lack of options (and often a lack of pain in these patients), revision of a subluxated or dislocated proximal humeral hemiarthroplasty endoprosthesis was not routinely performed. Recent work, however, has shown that patients can be converted to a reverse total shoulder allograft prosthetic composite (APC), with improvements in shoulder function and a relatively low rate of complications, offering a way to potentially improve functional outcomes in these patients 35 .…”
Section: Endoprosthetic Reconstructionmentioning
confidence: 99%